Comparıng The Influence of Force Traınıngs Applıed Wıth Dıfferent Methods - Sinan Akın; Oğuzhan Yuksel; Ali Turker (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to examine the influence different models of force trainings on balance values. In the research, 30 volunteer participants including 20 experimental (experiment A, experiment B) and 10 control aged between 18-22 have taken part. Volunteer participants partaking in experiment group have been incorporated into different force trainings of 3 days in a week during eight weeks. Training program 4. It has been modified their 1 maximum ranks (1TM) by being identified again at the end of the week. While the participants taking part in Experiment A (n=10) were given classic force training, those taking part in Experiment B (n=10) were given super slow motion force training. The participants in control group have gone on their routine daily lives. Before and after the training period, the values of Star Excursion Balance Test (SEBT) have been recorded. The values of Skewness amp; Kurtosis have been looked up to retain whether the datum obtained show normal distribution or not. When Repeated Measure ANOVA (Repeated Measure Anova) test was being applied to identify the differences between groups, Simple Effect Test has been implemented to determine the development level in the group. Significance level has been determined as p lt; 0.05. According to the results of Repeated measures Anova test, even though the significant change has been seen when the differences in the values of left foot star balance test in both experiment group were compared before and after the training period, a statistically significant difference has been determined in the values of right foot star balance test. According to the Simple Effect Test results, while the increase in the classic force training (experiment A) group is meaningless,it has been found that the increase in Super Slow Motion force training (experiment B) group is statistically meaningful. The results obtained show that classic and super slow motion force trainings have contributed to the development of force after the implementation period. Depending on the force gaining, the development in the values of dynamic balance has been seen. However, depending on string out in terms of time of tending to concentric and eccentric muscular contraction in slow motion force trainings, its influence on balance performance has more come into prominence.